FA-4 Assessment of Estrous Cycle Using Ultrasound to Determine Time of Insemination In Banteng (Bos javanicus, d’Alton 1823) - Dedi Rahmat Setiadi; Muhammad Agil; Iis Afriantini; Tuty L Yusuf; Muchidin Noordin; Yohana Tri Hastuti; Setyaningsih Rambu Liwa; Jansen Manansang; Dondin Sajuthi (Hemera Zoa, 2018)
Banteng is considered as endangered species by the International Union for Conservation of Nature (IUCN). Banteng is currently distributed in Java, in Kalimantan [Indonesian Borneo], Sabah [part of Malaysian Borneo], Myanmar, Thailand, Cambodia and, probably Lao PDR and Vietnam (1). The populations in the Asian mainland have decreased by about 80% in the last decades. The total number of wild banteng is estimated to about 5,000-8,000 animals. No population has more than 500 animals, only a few have more than 50. Reasons for the population decline are reduction of habitat, poaching, hybridisation with domesticated cattle, and infections with cattle diseases (4).Since the wild population has been declining continously and the numbers of individual are getting smaller, therefore captive breeding is urgently needed in order to support the conservation of Banteng sustainably. Although breeding program of Banteng is important, but information about the reproductive biology of Banteng is very limited. Breeding programs in Banteng can be done by natural mating or using assisted reproductive technology such as artificial insemination (AI). The aplication of AI in Banteng can support Banteng conservation program in order to increase heterozygosity, prevent inbreeding and possible to use of the Banteng bulls from different facilities for AI of females in all breeding facilities of Banteng.AI applications require information on the estrous cycle and estrous signs to determine the precise AI time. Clinical signs of estrous in Banteng is difficult to observe, therefore determining the time of AI must be done through rectal palpation and ultrasonography. The objectives of  this research is to assess estrous cycle to determine time of insemination.